A randomised crossover trial comparing photobiomodulation therapy with other recovery strategies in CrossFit athletes - Paulo Henrique Gusmão Nogueira Martins; Shaiane Silva Tomazoni; Caroline dos Santos Monteiro Machado; Amanda Lima Pereira; Henrique Dantas Pinto; Matheus Marinho Aguiar Lino; Neide Firmo Ribeiro; Luana Barbosa Dias; Ivo de Oliveira Aleixo Junior; Marcelo Ferreira Duarte de Oliveira; Older Manoel de Araújo-Silva; Thiago De Marchi; et al. (PLoS ONE, 2026)
Background This study compared the effects of different therapeutic modalities on recovery following the workout of the day (WOD) in CrossFit athletes, focusing on reducing muscle damage and improving functional performance. Methods In a randomised, controlled, crossover design, twelve CrossFit athletes underwent four post-WOD recovery interventions across four weeks: passive recovery (PR), intermittent pneumatic compression (IPC), extracorporeal shock wave therapy (ESWT), and photobiomodulation therapy combined with a static magnetic field (PBMT-sMF). Assessments were conducted at baseline, and at 1, 24, and 48 hours post-WOD. The primary outcome was vertical jump performance (countermovement jump [CMJ] height) at 1-hour post-WOD; secondary outcomes included lactate dehydrogenase (LDH) levels, superoxide dismutase (SOD) and catalase (CAT) activity, thiobarbituric acid reactive substances (TBARS), carbonylated proteins, perceived exertion, and intervention satisfaction. Results There was no significant difference between interventions in CMJ height at 1-hour post-WOD. In contrast, PBMT-sMF outperformed the other interventions in the secondary outcomes. PBMT-sMF significantly improved CMJ height at 24 and 48 hours compared with PR (p < 0.05) and led to greater reductions in LDH at both time points (p < 0.05 and p < 0.001, respectively). PBMT-sMF also produced lower TBARS and carbonylated protein levels, with higher CAT and SOD activities at 24 and 48 hours (p < 0.05 and p < 0.0001, respectively). CAT and SOD activities were also significantly elevated at 1 hour post-WOD compared with PR (p < 0.05). Conclusions PBMT-sMF may be an effective recovery strategy for CrossFit athletes, with its benefits possibly related to the modulation of oxidative stress as an underlying mechanism. Trial registration Trial registration number: NCT06628609 .